Meritve kakovostnih parametrov za modeliranje prvega vala onesnaženih voda s cestnih površin - Krzyk, Mario (Gradbeni vestnik, 2013)
Peak concentrations of pollutants in stormwater effluent occur in the early stages of precipitation known as the "first flush". To avoid overloading of waste water treatment plants and sewage channels, retaining pools of rain water should be built on joint sewage systems. After the ATV regulations in dimensioning of retaining pools for the retension of the first flush it is necesary to consider approx. 30 parameters. One of the most important indicator of poluted water is COD - chemical oxygen demand, which was analysedin detail. In the paper the results of own multi-year measurements of contaminated rainwater from the roads are presented and compared with sewage channel wastewater.
Keywords: ceste; kakovost; kemijska poraba kisika; kovine; onesnaženost voda; suspendirane snovi; zadrževalni bazeni